Lesson study with sharing and jumping tasks in online mathematics classrooms for rural area students - Tanujaya, Benidiktus; Prahmana, Rully Charitas Indra; Mumu, Jeinne (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2023)
Due to the poor instruction process during the Covid-19 Pandemic, especially in mathematics, students frequently need help with data literacy. To overcome these obstacles, they must improve their thinking skills. This study aims to enhance the quality of mathematics instruction, especially students' thinking skills, by implementing Lesson Study to develop sharing and jumping tasks. This qualitative descriptive research was conducted at one of the senior high schools and universities in Manokwari, West Papua, with their students as the research subject. The lesson study was implemented in two cycles through instruction at school and lectures at the university. The lesson study consists of three processes: plan, do, and see. The hypothetical learning trajectory was developed at the lesson design stage and then tested at the teaching-learning stage. The open class results were then analyzed during the reflection step to redesign the sharing and jumping tasks. The success of the research was determined through field notes taken from teachers and students. The frequency distribution table is used as the topic matter. The findings revealed that students' thinking skills developed, indicating they were more interested than in the previous teaching and learning process. The learning process was more exciting and enhanced conceptual comprehension. Because learning was communicable, students were more satisfied. They were more engaged and required further thought to comprehend the topic matter. Also, they produce a variety of responses, which is only feasible if they are capable of critical thought.